Carios kelleyi (Acari: Ixodida: Argasidae) Infected With Rickettsial Agents Documented Infesting Housing in Kansas, United States. Issue 6 (19th May 2021) - Nadolny, Robyn M; Kennedy, Ashley C; Rodgers, James M; Vincent, Zachary T; Cornman, Hannah; Haynes, Scott A; Casal, Cory; Robbins, Richard G; Richards, Allen L; Jiang, Ju; Farris, Christina M
Abstract: During September–December 2018, 25 live ticks were collected on-post at Fort Leavenworth, Kansas, in a home with a history of bat occupancy. Nine ticks were sent to the Army Public Health Center Tick-Borne Disease Laboratory and were identified as Carios kelleyi (Cooley and Kohls, 1941 ), a species that seldom bites humans but that may search for other sources of blood meals, including humans, when bats are removed from human dwellings. The ticks were tested for numerous agents of human disease. Rickettsia lusitaniae was identified by multilocus sequence typing to be present in two ticks, marking the first detection of this Rickettsia agent in the United States and in this species of tick. Two other Rickettsia spp. were also detected, including an endosymbiont previously associated with C. kelleyi and a possible novel Rickettsia species. The potential roles of C . kelleyi and bats in peridomestic Rickettsia transmission cycles warrant further investigation.